Self-repairing conductive polymer adhesive, preparation method thereof and lithium ion battery

Through the preparation method of self-healing conductive polymer adhesive, the problems of unenvironmental protection and high energy consumption of lithium-ion battery adhesives are solved, and the self-healing function and performance of the battery are improved.

CN119775934AActive Publication Date: 2025-04-08SHENZHEN YULIAN NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510271408.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-08
Publication Date
2025-04-08
Estimated Expiration
2045-03-08

AI Technical Summary

Technical Problem

Existing lithium-ion battery adhesives have problems such as uneco-friendly, high energy consumption, expensive price, poor water solubility and inability to effectively inhibit the volume expansion of silicon-based materials.

Method used

The self-healing conductive polymer adhesive is prepared by the pre-polymerization, repolymerization, emulsification and post-polymerization steps to prepare a conductive polymer adhesive with self-healing function. The method includes polymerization of polyether polyol or polyester polyol with diisocyanate, adding hydrophilic chain extenders and acrylates to improve the wettability of the electrolyte, and forming a reversible crosslinking reaction to achieve the self-healing function of the adhesive by adding an emulsifier and a crosslinking agent.

Benefits of technology

The self-healing function of lithium-ion battery adhesive is realized, the cycle stability, capacity retention and rate performance of the battery are improved, the service life of the battery is extended, and the battery is excellent in hydrophilicity, electrolyte wetting and ionic conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775934A_ABST
    Figure CN119775934A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a self-repairing conductive polymer adhesive. The preparation method comprises the following steps in parts by weight: a pre-polymerization step, a re-polymerization step, an emulsification step and a post-polymerization step. The invention also provides a self-repairing conductive polymer adhesive and a lithium ion battery comprising the self-repairing conductive polymer adhesive. The self-repairing conductive polymer adhesive has excellent adhesion and solubility, can effectively buffer structural tension generated by expansion and contraction of an electrode structure in the charging and discharging process, has excellent hydrophilicity, is good in electrolyte wettability, high in ionic conductivity and good in dispersion effect, and is not prone to demulsification under long-time stirring. Compared with a traditional SBR adhesive, the ionic conductivity is better. And meanwhile, the self-repairing conductive polymer adhesive also has self-healing property and can be self-repaired after structural damage caused by electrode expansion, so that the stability of the battery is ensured, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a self-repairing conductive polymer adhesive and a preparation method thereof, and also to a lithium ion battery. Background Art

[0002] As an efficient, reliable and environmentally friendly energy storage technology, lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and energy storage systems, and have promoted the development of renewable energy and electric transportation. One of the core components of lithium-ion batteries is the negative electrode material, which is made of active substances, binders and additives into a paste adhesive, which is then applied to both sides of the copper foil and rolled. The negative electrode conductive adhesive plays an important role in lithium-ion batteries. It is responsible for fixing the active substances in the negative electrode material on the electrode sheet and providing a uniform electron conduction path. At the same time, it inhibits the volume expansion caused by battery charging and discharging, enhances the mechanical stability of the electrode and protects the negative electrode material.

[0003] At present, the negative electrode slurry of lithium-ion batteries mainly uses styrene-butadiene rubber (SBR) as a binder. SBR is a mature industrial binder, but it has problems such as low ionic conductivity, swelling, easy demulsification under long-term stirring, and poor dispersion effect compared to CMC. Low ionic conductivity will increase electrode resistance and reduce capacitance, while swelling will destroy the electrode structure and reduce overall performance. There is no self-healing property, resulting in loss of function after the molecular structure is damaged. In order to solve these problems, researchers are looking for new conductive polymer negative electrode binders to reduce battery internal resistance and improve overall performance.

[0004] In this aspect of research, on the one hand, there is the addition of fluoride to the adhesive polymer to improve its performance. However, the addition of fluoride cannot effectively inhibit the volume expansion of silicon-based materials, and as a fluorine-containing oily adhesive, it is not environmentally friendly, has high energy consumption, is expensive, and is not conducive to the health of operators. On the other hand, there is the use of high molecular polysaccharides to make adhesives, which have better environmental performance and are relatively cheap. However, its performance cannot meet the current standards for commercial applications of lithium batteries, and the polysaccharide polymers used, such as chitosan, have poor dispersibility in aqueous solvents, which brings new problems to the electrode preparation process. Summary of the invention

[0005] In view of this, the present invention provides a self-healing conductive polymer adhesive and a preparation method thereof. The present invention also provides a lithium-ion battery to solve the problems of existing lithium-ion battery adhesives, such as being environmentally unfriendly, high energy consumption, high price, poor water solubility, and inability to effectively inhibit the volume expansion of silicon-based materials.

[0006] In a first aspect, the present invention provides a method for preparing a self-healing conductive polymer adhesive, comprising the following steps in parts by weight: Prepolymerization: provide a first reaction container and add 130-150 parts of polyether polyol or polyester polyol thereto, heat the first reaction container to 50-70°C, then add 40-60 parts of diisocyanate and 0.2-1 parts of organic tin catalyst or organic amine catalyst thereto, heat the first reaction container to 70-80°C and maintain for 0.5-3 hours, then add 1-3 parts of hydrophilic chain extender to the first reaction container, adjust the temperature of the first reaction container to 75-85°C, stir and react for 6-8 hours, and obtain a prepolymer after the reaction is completed; Repolymerization: adjusting the temperature of the first reaction container to 40-50°C and adding 30-50 parts of acrylate to the first reaction container, then heating the first reaction container to 70-80°C and maintaining for 1-5 hours, and after the reaction is completed, cooling the first reaction container to room temperature to obtain a repolymer; Emulsification: transferring the repolymer to an emulsification container and adding 250-300 parts of distilled water and 1-5 parts of TEA to the emulsification container to obtain an emulsified system, stirring the emulsified system for 0.5-3 h, and then adding 100-150 parts of styrene, 50-100 parts of a crosslinking agent and 1-5 parts of an emulsifier to the emulsified system, and continuing to stir the emulsified system for 0.5-3 h to obtain an emulsion system; Post-polymerization: The emulsion system is transferred to a second reaction container and heated to 70-90° C., 1-3 parts of a polymerization initiator are added thereto while stirring the emulsion system, and the stirring reaction is continued for 4-8 hours. After the reaction is completed, the second reaction container is cooled to room temperature to obtain a self-healing conductive polymer adhesive.

[0007] The preparation method of the self-healing conductive polymer adhesive of the present invention includes a pre-polymerization step, a re-polymerization step, an emulsification step and a post-polymerization step. In the pre-polymerization step, under the catalytic action of an organic tin catalyst or an organic amine catalyst, a polyether polyol or a polyester polyol reacts with a diisocyanate to generate a polymer with NCO at both ends, and the polymer with NCO at both ends reacts with a hydrophilic chain extender to obtain a pre-polymer with high molecular weight and high cross-linking degree. The hydrophilic chain extender can react with the functional groups on the linear polymer chain to extend the molecular chain and increase the molecular weight, and is used to improve the mechanical properties and process properties of the self-healing conductive polymer of lithium ion batteries. In the re-polymerization step, since acrylate has excellent electrolyte wettability, the pre-polymer modified by acrylate can significantly improve the electrolyte wettability of the self-healing conductive polymer adhesive and improve the rate performance of the battery. In the emulsification step, the newly added substance can be evenly dispersed by adding an emulsifier, especially water-insoluble reactive monomers such as styrene. After adding the emulsifier, water-insoluble reaction substances such as styrene can form micelles in the solution, evenly dispersed in the reaction system of the aqueous solution, and participate in the subsequent reaction. In the post-polymerization step, the styrene and cross-linking agent added in the previous step are emulsified and mixed evenly, and further under the initiation of the initiator, the emulsion system undergoes polymerization reaction again in the aqueous medium. By adding a cross-linking agent, the cross-linking agent and the polymer can be induced to undergo a cross-linking reaction, and this cross-linking reaction is a reversible process. This reversible reaction is conducive to the self-healing conductive polymer adhesive to maintain the adhesive properties of the adhesive through a reversible cross-linking reaction under different pressure states, thereby realizing the self-healing function of the adhesive. Triethylamine is used to prepare polyurethane, which plays a role in counterbalancing the acidic ions in the polymer main chain. The polyurethane prepolymer previously formed can be post-polymerized through the post-polymerization step, which can further increase the molecular weight of the polymer chain, and at the same time, a high solid content, low viscosity emulsion with a multivariate distribution of latex particle size is prepared by multiple initiation of nucleation.

[0008] Preferably, in the prepolymerization step, the polyether polyol is polytetramethylene ether glycol, polyoxypropylene glycol or tetramethylene ether glycol, the polyester polyol is polyethylene terephthalate-1,4-cyclohexane dimethanol ester, polycaprolactone polyol or polycarbonate diol, and the diisocyanate is isophorone diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate or methylcyclohexane diisocyanate. Suitable polyether polyols or polyester polyols and diisocyanates can further improve the mechanical properties and process properties of the self-healing conductive polymer adhesive.

[0009] Preferably, in the prepolymerization step, the organic tin catalyst is dibutyltin dilaurate, tributyltin alcohol or tributyltin bis(phenyl)hydrazine, the organic amine catalyst is triethylamine, pyridine or pyrrolidine, and the hydrophilic chain extender is dimethylolpropionic acid (DMPA) or 4,4-diaminodiphenyl sulfide. Suitable catalysts can significantly increase the reaction rate and the uniformity of the polymer molecular weight and reduce the reaction time.

[0010] Preferably, in the prepolymerization step, 140 parts of polytetramethylene glycol are added to the first reaction container, the first reaction container is heated to 60° C., 50 parts of isophorone diisocyanate and 0.5 parts of dibutyltin dilaurate are added thereto, and the first reaction container is heated to 75° C. and maintained for 1 hour; Then, 2 parts of dimethylol propionic acid are added to the first reaction container, the temperature of the first reaction container is adjusted to 80°C, and the reaction is stirred at 400-800 RPM for 6-8 hours, and the prepolymer is obtained after the reaction is completed. The appropriate amount of reaction monomers and reaction steps can significantly increase the reaction rate and the uniformity of the polymer molecular weight, and reduce the reaction time.

[0011] Preferably, in the repolymerization step, the acrylate is methyl acrylate, ethyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate or butyl acrylate. Suitable acrylates can fully participate in the polymer modification process and can also effectively improve the hydrophilicity and wetting properties of the self-healing conductive polymer adhesive in the electrolyte.

[0012] Preferably, in the repolymerization step, the temperature of the first reaction container is adjusted to 45°C and 40 parts of methyl methacrylate are added to the first reaction container, and then the first reaction container is heated to 75°C and maintained for 3 hours. After the reaction is completed, the first reaction container is cooled to room temperature to obtain a repolymer. Appropriate polymerization reaction process conditions and dosage can improve the reaction progress and reduce the yield of by-products.

[0013] Preferably, in the emulsification step, the cross-linking agent is boric acid, and the emulsifier is sodium lauryl sulfate or dodecylphenol polyoxyethylene ether; The stirring speed is 600-1500 RPM. The borate bond can ensure that the sample has a good mechanical strength, and the borate bond can undergo a reversible hydrolysis reaction, and this dynamic process is also conducive to self-repairing behavior. A suitable emulsifier can make each reactant form micelles in the solution and evenly disperse in the reaction system of the aqueous solution to participate in the reaction.

[0014] Preferably, in the post-polymerization step, the polymerization initiator is a mixed solution with a mass fraction of 0.3% to 1.5%, and the solute of the polymerization initiator is sodium persulfate, potassium persulfate or ammonium persulfate; The stirring speed is 300 to 800 RPM. Selecting a polymerization initiator in a mixed solution state can help the polymerization initiator to fully contact the reactants and fully initiate polymerization, thereby ensuring that the polymerization reaction is thorough and the product has uniform molecular weight and structure.

[0015] In a second aspect, the present invention further provides a self-healing conductive polymer adhesive, wherein the self-healing conductive polymer adhesive is prepared by the preparation method of the self-healing conductive polymer adhesive described in any one of the first aspects.

[0016] The self-healing conductive polymer adhesive of the present invention has excellent adhesion and solubility, can effectively buffer the structural tension generated by the expansion and contraction of the electrode structure during the charge and discharge process, and has excellent hydrophilicity, good electrolyte wettability, high ion conductivity, good dispersion effect, and is not easy to demulsify under long-term stirring. Compared with traditional SBR adhesives, the ion conductivity is better. At the same time, the self-healing conductive polymer adhesive of the present invention also has self-healing properties, and can self-repair after the electrode expansion causes structural damage, ensuring the stability of the battery and extending the service life.

[0017] In a third aspect, the present invention further provides a lithium-ion battery, which includes the self-healing conductive polymer adhesive described in the second aspect.

[0018] The lithium ion battery of the invention adopts a self-repairing conductive polymer adhesive, and the lithium ion battery has excellent cycle stability, capacity retention rate and rate performance.

[0019] Advantages of the present invention will be partially set forth in the following description, and partly will be obvious from the description, or may be learned through implementation of the embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the content of the present invention, it is described in detail below with reference to the accompanying drawings and specific embodiments.

[0021] Figure 1 This is the result of the normal temperature cycle performance comparison test; Figure 2 This is the test result of a single-sided pole piece passing through a steel needle; Figure 3 This is the test result of the internal resistance of the electrode; Figure 4 This is the DC internal resistance test result diagram. DETAILED DESCRIPTION

[0022] The following is a preferred embodiment of the present invention. It should be noted that a person skilled in the art may make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

[0023] The following describes in detail the self-healing conductive polymer adhesive of the present application and its preparation method, as well as a lithium-ion battery assembled using the self-healing conductive polymer adhesive of the present application as a negative electrode adhesive through specific embodiments. Example 1

[0024] A method for preparing a self-healing conductive polymer adhesive comprises the following steps in parts by weight: Prepolymerization step: Provide a stainless steel reactor and add 135 g of polyoxypropylene glycol therein and heat the stainless steel reactor to 70°C. After the heating is completed, add 45 g of methylcyclohexane diisocyanate and 0.2 g of triethylamine to the stainless steel reactor, and then heat the stainless steel reactor to 70°C and maintain for 3 hours. After the reaction is completed, add 1 g of dimethylol propionic acid to the stainless steel reactor, adjust the temperature of the stainless steel reactor to 75°C again, stir the mixed system in the stainless steel reactor at 400 RPM for 7 hours, and obtain a prepolymer after the stirring reaction is completed.

[0025] Repolymerization step: adjust the temperature of the stainless steel reactor to 40°C and add 40 parts of methyl acrylate into the stainless steel reactor, then heat the stainless steel reactor to 75°C and maintain for 1 hour. After the reaction is completed, cool the stainless steel reactor to room temperature to obtain a repolymer.

[0026] Emulsification step: transfer the aforementioned repolymer to an emulsification container and add 250 g of distilled water and 2 g of neutralizer TEA (triethylamine) to the emulsification container to obtain an emulsified system, stir the emulsified system at 1500 RPM for 0.5 h, then add 100 g of styrene, 50 g of boric acid and 1 g of dodecylphenol polyoxyethylene ether to the emulsified system, and continue to stir the emulsified system at 1500 RPM for 0.5 h to obtain an emulsion system.

[0027] Post-polymerization step: transfer the above-mentioned emulsion system to a stainless steel reactor and heat it to 70°C. While stirring the emulsion system, slowly add 2 g of a 0.3% potassium persulfate solution into it. Stir the emulsion system at a speed of 300 RPM for 6 h while adding. After the stirring reaction is completed, cool the stainless steel reactor to room temperature to obtain a self-healing conductive polymer adhesive. Example 2

[0028] A method for preparing a self-healing conductive polymer adhesive comprises the following steps in parts by weight: Prepolymerization step: Provide a stainless steel reactor and add 130 g of polycaprolactone polyol into it and heat the stainless steel reactor to 60°C. After the heating is completed, add 40 g of diphenylmethane diisocyanate and 0.3 g of tributyltin alcohol into the stainless steel reactor, and then heat the stainless steel reactor to 70°C and maintain for 2 hours. After the reaction is completed, add 2 g of hydrophilic chain extender 4,4-diaminodiphenyl sulfide into the stainless steel reactor, adjust the temperature of the stainless steel reactor to 80°C again, stir the mixed system in the stainless steel reactor at 400RPM for 8 hours, and obtain the prepolymer after the stirring reaction is completed.

[0029] Repolymerization step: adjust the temperature of the stainless steel reactor to 40°C and add 30 parts of ethyl acrylate into the stainless steel reactor, then heat the stainless steel reactor to 70°C and maintain for 2 hours. After the reaction is completed, cool the stainless steel reactor to room temperature to obtain a repolymer.

[0030] Emulsification step: transfer the aforementioned repolymer to an emulsification container and add 260 g of distilled water and 1 g of neutralizer TEA (triethylamine) to the emulsification container to obtain an emulsified system, stir the emulsified system at 600 RPM for 1 h, then add 130 g of styrene, 60 g of boric acid and 2 g of sodium dodecyl sulfate to the emulsified system, and continue to stir the emulsified system at 600 RPM for 1 h to obtain an emulsion system.

[0031] Post-polymerization step: transfer the above-mentioned emulsion system to a stainless steel reactor and heat it to 75°C. While stirring the emulsion system, slowly add 1 g of 1.2% ammonium persulfate solution into it. Stir the emulsion system at a speed of 400 RPM for 8 h while adding. After the stirring reaction is completed, cool the stainless steel reactor to room temperature to obtain a self-healing conductive polymer adhesive. Example 3

[0032] A method for preparing a self-healing conductive polymer adhesive comprises the following steps in parts by weight: Prepolymerization step: Provide a stainless steel reactor and add 140 g of polytetramethylene glycol thereto and heat the stainless steel reactor to 60°C. After the heating is completed, add 50 g of isophorone diisocyanate and 0.5 g of dibutyltin dilaurate to the stainless steel reactor, and then heat the stainless steel reactor to 75°C and maintain for 1 hour. After the reaction is completed, add 2 g of hydrophilic chain extender dimethylol propionic acid to the stainless steel reactor, adjust the temperature of the stainless steel reactor to 80°C again, stir the mixed system in the stainless steel reactor at 600RPM for 7 hours, and obtain a prepolymer after the stirring reaction is completed.

[0033] Repolymerization step: adjust the temperature of the stainless steel reactor to 45°C and add 40 parts of methyl 2-methacrylate into the stainless steel reactor, then heat the stainless steel reactor to 75°C and maintain for 3 hours. After the reaction is completed, cool the stainless steel reactor to room temperature to obtain a repolymer.

[0034] Emulsification step: the aforementioned repolymer was transferred to an emulsification container, and 280 g of distilled water and 3 g of neutralizing agent TEA (triethylamine) were added to the emulsification container to obtain an emulsified system, and the emulsified system was stirred at 1000 RPM for 2 h. Then, 120 g of styrene, 80 g of boric acid and 3 g of sodium dodecyl sulfate were added to the emulsified system, and the emulsified system was continued to be stirred at 1000 RPM for 2 h to obtain an emulsion system.

[0035] Post-polymerization step: The above-mentioned emulsion system was transferred to a stainless steel reactor and heated to 80°C. While stirring the emulsion system, 2 g of a 1% sodium persulfate solution was slowly added thereto. The emulsion system was stirred at a speed of 500 RPM for 6 h. After the stirring reaction was completed, the stainless steel reactor was cooled to room temperature to obtain a self-healing conductive polymer adhesive. Example 4

[0036] A method for preparing a self-healing conductive polymer adhesive comprises the following steps in parts by weight: Prepolymerization step: Provide a stainless steel reactor and add 150 g of polyethylene terephthalate-1,4-cyclohexane dimethanol ester thereto and heat the stainless steel reactor to 70°C. After the heating is completed, 60 g of hexamethylene diisocyanate and 0.8 g of pyrrolidine are added to the stainless steel reactor, and the stainless steel reactor is heated to 80°C and maintained for 1 hour. After the reaction is completed, 3 g of hydrophilic chain extender 4,4-diaminodiphenyl sulfide is added to the stainless steel reactor, and the temperature of the stainless steel reactor is adjusted to 85°C again. The mixed system in the stainless steel reactor is stirred at 600 RPM for 8 hours, and the prepolymer is obtained after the stirring reaction is completed.

[0037] Repolymerization step: adjust the temperature of the stainless steel reactor to 50°C and add 50 parts of ethyl 2-methacrylate into the stainless steel reactor, then heat the stainless steel reactor to 80°C and maintain for 5 hours. After the reaction is completed, cool the stainless steel reactor to room temperature to obtain a repolymer.

[0038] Emulsification step: the aforementioned repolymer was transferred to an emulsification container, and 290 g of distilled water and 5 g of neutralizer TEA (triethylamine) were added to the emulsification container to obtain an emulsified system, and the emulsified system was stirred at 800 RPM for 3 h. Then, 150 g of styrene, 100 g of boric acid and 5 g of sodium dodecyl sulfate were added to the emulsified system, and the emulsified system was continued to be stirred at 800 RPM for 3 h to obtain an emulsion system.

[0039] Post-polymerization step: The above-mentioned emulsion system was transferred to a stainless steel reactor and heated to 85°C. While stirring the emulsion system, 3 g of a 0.8% potassium persulfate solution was slowly added thereto. The emulsion system was stirred at a speed of 800 RPM for 4 h. After the stirring reaction was completed, the stainless steel reactor was cooled to room temperature to obtain a self-healing conductive polymer adhesive. Example 5

[0040] A method for preparing a self-healing conductive polymer adhesive comprises the following steps in parts by weight: Prepolymerization step: Provide a stainless steel reactor and add 145 g of tetrahydrofuran-propylene oxide copolymer glycol into it and heat the stainless steel reactor to 60°C. After the heating is completed, 55 g of toluene diisocyanate and 1 g of tributyltin are added to the stainless steel reactor, and the stainless steel reactor is heated to 80°C and maintained for 0.5 h. After the reaction is completed, 3 g of hydrophilic chain extender dimethylol propionic acid is added to the stainless steel reactor, and the temperature of the stainless steel reactor is adjusted to 85°C again. The mixed system in the stainless steel reactor is stirred at 800RPM for 6 h, and the prepolymer is obtained after the stirring reaction is completed.

[0041] Repolymerization step: adjust the temperature of the stainless steel reactor to 45°C and add 40 parts of butyl acrylate into the stainless steel reactor, then heat the stainless steel reactor to 80°C and maintain for 4 hours. After the reaction is completed, cool the stainless steel reactor to room temperature to obtain a repolymer.

[0042] Emulsification step: transfer the aforementioned repolymer to an emulsification container and add 300 g of distilled water and 4 g of neutralizer TEA (triethylamine) to the emulsification container to obtain an emulsified system, stir the emulsified system at 1200 RPM for 2 h, then add 120 g of styrene, 90 g of boric acid and 4 g of dodecylphenol polyoxyethylene ether to the emulsified system, continue to stir the emulsified system at 1200 RPM for 2 h to obtain an emulsion system.

[0043] Post-polymerization step: transfer the above-mentioned emulsion system to a stainless steel reactor and heat it to 90°C. While stirring the emulsion system, slowly add 2 g of a 1.5% sodium persulfate solution into it. Stir the emulsion system at a speed of 600 RPM for 5 h while adding. After the stirring reaction is completed, cool the stainless steel reactor to room temperature to obtain a self-healing conductive polymer adhesive.

[0044] Effect Example 1: Physical property test of self-healing conductive polymer adhesive The self-healing conductive polymer adhesive prepared in Examples 1-5 was taken as a test sample, and the commercially available SBR binder TRD104A produced by Japan Synthetic Rubber Company was taken as a control sample. The test sample and the control sample were simultaneously subjected to physical tests. The test indicators included Tg, viscosity, pH and solid content of the test adhesive. The test results are shown in Table 1.

[0045] Table 1 Physical test results TRD104A Example 1 Example 2 Example 3 Example 4 Example 5 Tg / ℃ 0.0 0.0 -5.8 -4.3 -3.8 -1.4 Viscosity / mPa·s 100 1512 1531 1545 1577 1603 pH 7.0 8.8 9.2 9.1 8.9 9.1 Solid content 45% 40% 40% 40% 40% 40% As shown in the physical test results in Table 1, compared with the TRD104A SBR binder, the self-healing conductive polymer adhesive prepared in Examples 1-5 has a greater viscosity and stronger adhesion under the premise of similar or even lower solid content. The results show that the self-healing conductive polymer adhesive prepared in this application has better and more excellent adhesion properties.

[0046] Effect Example 2: Normal Temperature Cycle Performance Comparison Test The self-healing conductive polymer adhesive prepared in Example 3 was taken as a test sample, and the commercially available SBR binder TRD104A produced by Japan Synthetic Rubber Company was taken as a control sample. The test sample and the control sample were simultaneously subjected to a room temperature cycle performance comparison test. Test equipment: Xinwei battery test cabinet, internal resistance tester, multimeter, digital caliper. Test method: Charge to 4.2 V with a charging current of 0.5 C and a cut-off current of 0.01 C at a temperature of 25±2°C, leave for 10 min, then discharge to 2.75 V with a charging current of 1 C, leave for 10 min, and repeat the above steps 500 times. Test requirements: The capacity retention rate is ≥80% after 500 cycles of 1 C / 1 C. See the attached test results. Figure 1 .

[0047] like Figure 1 As shown, in the first 200 cycles, the capacity retention rates of the test samples and the control samples were basically the same. At 200 to 300 cycles, the capacity retention rate of the test samples began to widen the gap with the capacity retention rate of the control samples, and the capacity retention rate of the test samples was better than that of the control samples. This shows that as the number of cycles increases, the internal pole pieces of the battery begin to be gradually damaged, and the test samples have self-repairing properties that can slow down the damage to the pole pieces, so they can have better capacity retention rates than the control samples in long-term and long-number cycles. At 500 cycles, the capacity retention rate of the test samples will be 1 to 2% higher than that of the control samples. It can be seen that the cycle life of the test samples is better than that of the control samples, indicating that the self-repairing properties are effective and help extend the service life of lithium batteries.

[0048] Effect Example 3: Single-sided pole piece steel needle test The self-healing conductive polymer adhesive prepared in Example 3 was taken as a test sample, and the commercially available SBR adhesive TRD104A produced by Japan Synthetic Rubber Co., Ltd. was taken as a control sample. The test sample and the control sample were simultaneously subjected to a single-sided pole piece steel needle test.

[0049] Test method: (1) Prepare several pole pieces according to the pole piece preparation method. From coating to roller pressing: observe the slurry sedimentation and stratification, gel abnormalities, pole piece appearance shrinkage, bubbles, decarburization and other abnormalities, and calculate the pole piece yield rate. (2) Needle winding: Take the cold pressed pole piece (the compaction density is selected according to the actual application, the laboratory recommends the compaction density: 1.65 g / cm 3 ), starting from the largest winding needle (5mm), wrap the pole piece around the winding needle (diameter: 5 mm, 4 mm, 3 mm, 2 mm) in turn, and align the winding needle part with force. (3) Aim the objective lens at the bent tip, magnify it 100 times, and observe whether there is any crack. After unfolding, observe the shedding situation. The test results are attached. Figure 2 .

[0050] like Figure 2 As shown in the figure, when the diameter of the steel needle is 5 mm and 4 mm, there is no obvious difference between the test sample and the control sample. When the diameter of the steel needle reaches 3 mm, the pole piece of the control sample begins to partially fall off, while only a small part of the pole piece of the experimental sample falls off. When the diameter of the steel needle reaches 2 mm, most of the pole piece of the control sample has fallen off, while only a small part of the pole piece of the test sample still falls off. It can be seen that the pole piece made in Example 3 has better adhesion than the control sample.

[0051] Effect Example 4: Pole internal resistance test and DC internal resistance test According to the battery preparation process, the self-healing conductive polymer adhesive prepared in Example 3 and the SBR binder TRD104A were assembled together into a test battery, and the test battery was marked as JSR104A and GT901, respectively.

[0052] Pole internal resistance test: Cut the negative electrode sample into 100-200 mm wide, 220 mm long, and test the thickness of the slice. Place the test sample on the sample holder and adjust the height hand wheel so that the probe can maintain good contact with its surface. Turn on the power and preheat for 1 hour. Measure the resistivity value three times according to the operating procedures of the four-probe tester and take the average value. See the attached test results. Figure 3 .

[0053] DC internal resistance test: The battery is adjusted to different SOC states (battery remaining capacity 100%, 80%, 60%, 40%, 20%), and a DC resistance tester is used to test its 1 C&30 s DC resistance DCIR = (V 30s -V 0s) / I 1C The test results are shown in the attached Figure 4 .

[0054] like Figure 3 As shown, the electrode internal resistance of the SBR binder TRD104A in the three tests is higher than that of the self-healing conductive polymer adhesive prepared in Example 3. It can be seen that the self-healing conductive polymer adhesive prepared in Example 3 has better conductivity, and the corresponding prepared battery has better electrical performance.

[0055] like Figure 4 As shown, the DC resistance of the SBR binder TRD104A under different SOC states is greater than that of the self-healing conductive polymer adhesive prepared in Example 3. It can be seen that the self-healing conductive polymer adhesive prepared in Example 3 has better conductivity, and the corresponding prepared battery has better electrical properties.

[0056] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a self-healing conductive polymer adhesive, characterized in that: By weight The steps include: Prepolymerization: provide a first reaction container and add 130-150 parts of polyether polyol or polyester polyol thereto, heat the first reaction container to 50-70°C, then add 40-60 parts of diisocyanate and 0.2-1 parts of organic tin catalyst or organic amine catalyst thereto, heat the first reaction container to 70-80°C and maintain for 0.5-3 hours, then add 1-3 parts of hydrophilic chain extender to the first reaction container, adjust the temperature of the first reaction container to 75-85°C, stir and react for 6-8 hours, and obtain a prepolymer after the reaction is completed; Repolymerization: adjusting the temperature of the first reaction container to 40-50°C and adding 30-50 parts of acrylate to the first reaction container, then heating the first reaction container to 70-80°C and maintaining for 1-5 hours, and after the reaction is completed, cooling the first reaction container to room temperature to obtain a repolymer; Emulsification: transferring the repolymer to an emulsification container and adding 250-300 parts of distilled water and 1-5 parts of TEA to the emulsification container to obtain an emulsified system, stirring the emulsified system for 0.5-3 h, and then adding 100-150 parts of styrene, 50-100 parts of a crosslinking agent and 1-5 parts of an emulsifier to the emulsified system, and continuing to stir the emulsified system for 0.5-3 h to obtain an emulsion system; Post-polymerization: The emulsion system is transferred to a second reaction container and heated to 70-90° C., 1-3 parts of a polymerization initiator are added thereto while stirring the emulsion system, and the stirring reaction is continued for 4-8 hours. After the reaction is completed, the second reaction container is cooled to room temperature to obtain a self-healing conductive polymer adhesive.

2. The method for preparing the self-healing conductive polymer adhesive according to claim 1, characterized in that: In the pre-polymerization step, the polyether polyol is polytetramethylene ether glycol, polyoxypropylene glycol or tetramethylene ether glycol-oxypropylene copolymer glycol, the polyester polyol is polyethylene terephthalate-1,4-cyclohexane dimethanol ester, polycaprolactone polyol or polycarbonate diol, and the diisocyanate is isophorone diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate or methylcyclohexane diisocyanate.

3. The method for preparing the self-healing conductive polymer adhesive according to claim 1, characterized in that: In the prepolymerization step, the organic tin catalyst is dibutyltin dilaurate, tributyltin alcohol or tributyltin phenyl, the organic amine catalyst is triethylamine, pyridine or pyrrolidine, and the hydrophilic chain extender is dimethylolpropionic acid (DMPA) or 4,4-diaminodiphenyl sulfide.

4. The method for preparing the self-healing conductive polymer adhesive according to claim 1, characterized in that: In the prepolymerization step, 140 parts of polytetramethylene glycol are added to a first reaction container, and the first reaction container is heated to 60° C., and then 50 parts of isophorone diisocyanate and 0.5 parts of dibutyltin dilaurate are added thereto, and then the first reaction container is heated to 75° C. and maintained for 1 hour; then 2 parts of dimethylolpropionic acid are added to the first reaction container, and the temperature of the first reaction container is adjusted to 80° C., and the reaction is stirred at 400-800 RPM for 6-8 hours, and a prepolymer is obtained after the reaction is completed.

5. The method for preparing the self-healing conductive polymer adhesive according to claim 1, characterized in that: In the repolymerization step, the acrylic acid ester is methyl acrylate, ethyl acrylate, methyl 2-methacrylate, ethyl 2-methacrylate or butyl acrylate.

6. The method for preparing the self-healing conductive polymer adhesive according to claim 1, characterized in that: In the repolymerization step, the temperature of the first reaction container is adjusted to 45°C and 40 parts of methyl methacrylate are added to the first reaction container. The temperature of the first reaction container is then raised to 75°C and maintained for 3 hours. After the reaction is completed, the first reaction container is cooled to room temperature to obtain a repolymer.

7. The method for preparing the self-healing conductive polymer adhesive according to claim 1, characterized in that: In the emulsification step, the cross-linking agent is boric acid, and the emulsifier is sodium lauryl sulfate or dodecylphenol polyoxyethylene ether; The stirring speed is 600-1500 RPM.

8. The method for preparing the self-healing conductive polymer adhesive according to claim 1, characterized in that: In the post-polymerization step, the polymerization initiator is a mixed solution with a mass fraction of 0.3% to 1.5%, and the solute of the polymerization initiator is sodium persulfate, potassium persulfate or ammonium persulfate; The stirring speed is 300-800 RPM.

9. A self-healing conductive polymer adhesive, characterized in that: The self-healing conductive polymer adhesive is prepared by the preparation method of the self-healing conductive polymer adhesive according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The invention comprises the self-healing conductive polymer adhesive as claimed in claim 9.

Citation Information

Patent Citations

  • Self-healing lithium ion battery silicon-based negative electrode material and preparation method thereof

    CN112397718A

  • Flexible self-healing deep sea solid-state battery

    CN113921822A

  • Waterborne polyurethane adhesive as well as preparation method and application thereof

    CN118290661A

  • Lithium ion battery Si / C negative electrode aqueous binder and preparation method thereof

    CN119570428A

  • Negative electrode binder, and preparation method therefor and use thereof

    WO2025025499A1